Enhanced electrical and photocurrent characteristics of sol-gel derived Ni-doped PbTiO3 thin films. Issue 10 (July 2017) - Zhao, C.W.; Luo, B.C.; Guo, S.J.; Chen, C.L.
Abstract: Partial substitution of group 10 metal for titanium is predicted theoretically to be one of the most effective ways to decrease the band gap of PbTiO3 -based ferroelectric photovoltaic materials. It is therefore of interest to experimentally investigate their ferroelectric and photovoltaic properties. In this work, we focus on the electrical and photocurrent properties of Ni-doped PbTiO3 thin films prepared via a sol-gel route. The nickel incorporation does not modify the crystalline structure of PbTiO3 thin film, but it can increase the dielectric constant, ferroelectric polarization and photocurrent, and simultaneously decrease the band gap. The maximum remnant polarization ( P r ) of 58.1 μC/cm 2 is observed in PbTi0.8 Ni0.2 O3 thin film, and its photocurrent density is improved to be approximately one order larger than that of PbTiO3 thin film and simultaneously exhibits the polarization-dependent switching characteristic, which may be a promising choice for ferroelectric photovoltaic applications.